Oxidation of Methane to Methanol with Hydrogen Peroxide Using Supported Gold–Palladium Alloy Nanoparticles1. Issue 4 (11th December 2012) - Ab Rahim, Mohd Hasbi; Forde, Michael M.; Jenkins, Robert L.; Hammond, Ceri; He, Qian; Dimitratos, Nikolaos; Lopez‐Sanchez, Jose Antonio; Carley, Albert F.; Taylor, Stuart H.; Willock, David J.; Murphy, Damien M.; Kiely, Christopher J.; et al.
<x xml:space="preserve">Abstract</x> Direct and selective: Supported gold–palladium nanoparticles are active for the oxidation of methane, giving a high selectivity for the formation of methyl hydroperoxide and methanol, using hydrogen peroxide as the oxidant (see picture). The optimal methanol selectivity is achieved by performing the reaction in the presence of hydrogen peroxide that has been generated in situ from hydrogen and oxygen.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>